ENGARUH TERAPI SPIRITUAL DZIKIR TERHADAP KUALITAS HIDUP LANSIA MUSLIM PENGARUH TERAPI SPIRITUAL DZIKIR TERHADAP KUALITAS HIDUP LANSIA MUSLIM - siti aminah waluyo; Lestari Lestari; nabila Aprillia (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction the elderly population in Indonesia continues to increase. The elderly experience physical, psychological, social, and environmental changes that can be neutralized or eliminated by a strong spiritual life. The purpose of this study determine the effect of dzikir spiritual healing on the quality of life of Muslim elderly in in RW 005 Kelurahan Pondok Benda - Kota Tangerang. The research method used Quasy Experiment Design, One Group Pretest Posttest Design. The sample in this study were 34 respondents. The sampling technique used qouta sampling. Data collection was carried out by means of interviews using the World Health Organization-Quality of Life (WHOQOL) questionnaire. Data analysis to test the hypothesis can also be seen from the significance of the results of the Paired T- test Samples with p= 0,000. The results of the research before doing dzikir spiritual healing were good (18; 52.9%), with less physical domain (34; 100%), less psychological domain (34; 100%), less social domain (28; 82.4%) , and the environmental domain is less (30; 88.2%) and after dzikir spiritual healing the quality of life of the elderly is good (30; 88.2%), with good physical domain (22; 64.7%), good psychological domain. (16; 47.1%), good social domain (17; 50%), good environmental domain (18; 52.9%). Approach the need for the elderly to quality of life of the elderly who are undergoing dzikir spiritual healing. The conclusion is that there is an effect of dzikir spiritual healing on the quality of life of elderly Muslims in RW 005 Kelurahan Pondok Benda - Kota Tangerang.